Enhanced rabies surveillance in roadkill specimens by real-time RT-PCR. - Crystal M Gigante; Claire Hartloge; Rene Edgar Condori; Jordona D Kirby; Lauren Hovis; Kathleen M Nelson; Ryan Wallace; Yu Li; Richard B Chipman (PLoS Neglected Tropical Diseases)
Roadkill specimens are an important source of samples for enhanced rabies surveillance (ERS) in areas where other methods of sample collection may not be practical. However, the physical condition of roadkill specimens is unpredictable and, in many circumstances, unsatisfactory for rabies diagnostic testing by antigen detection methods. The high sensitivity of real-time reverse transcriptase PCR (RT-PCR) holds promise for rabies diagnostic testing of poor-quality samples. We conducted an evaluation of real-time RT-PCR to detect rabies virus RNA in roadkill samples. A total of 299 specimens were collected from raccoons (n = 232), skunks (n = 46), foxes (n = 17), coyotes (n = 2), a bobcat (n = 1), and a domestic cat (n = 1) across ten states during 2018 - 2021 in the United States. Eight samples (2.7%) were positive using the LN34 pan-lyssavirus real-time RT-PCR assay. These eight rabid animals in areas of high interest for wildlife rabies management would likely not have been identified otherwise. These findings support the use of real-time RT-PCR for samples that would typically be unsuitable for testing by widely used antigenic-based detection methods such as the direct fluorescent antibody test (DFA or FAT) and direct rapid immunohistochemistry test (DRIT).